The effects of runs-of-homozygosity on pig domestication and breeding - Lin Tao; Hang Liu; Adeniyi C. Adeola; Hai-Bing Xie; Shu-Tang Feng; Ya-Ping Zhang (BMC Genomics)
Abstract Background Since their domestication, recent inbreeding together with intensive artificial selection and population bottlenecks have allowed the prevalence of deleterious mutations and the increase of runs-of-homozygosity (ROH) in domestic pigs. This makes pigs a good model to understand the genetic underpinnings of inbreeding depression. Results Here we integrated a comprehensive dataset comprising 7239 domesticated pigs and wild boars genotyped by single nucleotide polymorphism (SNP) chips, along with phenotypic data encompassing growth, reproduction and disease-associated traits. Our study revealed differential ROH landscapes during domestication and artificial selection of Eurasian pigs. We observed associations between ROH burden and phenotypic traits such as body conformation and susceptibility to diseases like scrotal hernia. By examining associations of whole-genome and regional ROH burden with gene expression, we identified specific genes and pathways affected by inbreeding depression. Associations of regional ROH burden with gene expression also enabled the discovery of novel regulatory elements. Lastly, we inferred recessive lethal mutations by examining depletion of ROH in an inbred population with relatively small sample size, following by fine mapping with sequencing data. Conclusions These findings suggested that both phenotypic and genetic variations have been reshaped by inbreeding, and provided insights to the genetic mechanisms underlying inbreeding depression.